The Relationship Between Postpartum Physical Symptom Severity and Sleep Quality in Women with Cesarean Section - Melike Yılmaz; Nuriye Erbaş (Gazi Medical Journal)
Objective: This study was conducted to examine the relationship between postpartum physical symptom severity and sleep quality among women undergoing cesarean section. Methods: This descriptive cross-sectional study was conducted with a total of 193 women with cesarean section in a city hospital between October 14, 2019 and May 30, 2020. Data were collected using an individual characteristics form, the postpartum physical symptom severity scale (PPSSS) and Pittsburgh sleep quality index (PSQI). Data were evaluated using descriptive statistics, such as number and percentage distributions, t-test, analysis of variance (ANOVA), Mann-Whitney U test, Kruskal-Wallis H test, Pearson’s correlation analysis, and linear regression analysis. Results: The women’s PPSSS mean score was 10.38±5.92, suggesting low postpartum physical symptom severity. However, the most common physical symptoms in the fourth postpartum week were poor sleep quality/lack of sleep (85.5%) and perineal/incision pain (82.9%); and their least common physical symptoms were vaginal infection (9.8%) and urinary incontinence (11.4%). In addition, the women’s PSQI mean score was 8.57±3.53, and 83.9% of them had poor sleep quality. Conclusion: There was a statistically significant, positive, moderate relationship between postpartum physical symptom severity and sleep quality in women who underwent cesarean section (r=0.438; p=0.000) (p<0.05), whereby sleep quality decreased as postpartum physical symptom severity increased.